Hepatic Tumor Cell Morphology Plasticity under Physical Constraints in 3D Cultures Driven by YAP-mTOR Axis - Adam Frtús; Barbora Smolková; Mariia Uzhytchak; Mariia Lunova; Milan Jirsa; Martin Hof; Piotr Jurkiewicz; Vladimir I. Lozinsky; Lucie Wolfová; Yuriy Petrenko; Šárka Kubinová; Alexandr Dejneka; et al. (MDPI AG, 2020)
Recent studies undoubtedly show that the mammalian target of rapamycin (mTOR) and the Hippo-Yes-associated protein 1 (YAP) pathways are important mediators of mechanical cues. The crosstalk between these pathways as well as de-regulation of their signaling has been implicated in multiple tumor types, including liver tumors. Additionally, physical cues from 3D microenvironments have been identified to alter gene expression and differentiation of different cell lineages. However, it remains incompletely understood how physical constraints originated in 3D cultures affect cell plasticity and what the key mediators are of such process. In this work, we use collagen scaffolds as a model of a soft 3D microenvironment to alter cellular size and study the mechanotransduction that regulates that process. We show that the YAP-mTOR axis is a downstream effector of 3D cellular culture-driven mechanotransduction. Indeed, we found that cell mechanics, dictated by the physical constraints of 3D collagen scaffolds, profoundly affect cellular proliferation in a YAP-mTOR-mediated manner. Functionally, the YAP-mTOR connection is key to mediate cell plasticity in hepatic tumor cell lines. These findings expand the role of YAP-mTOR-driven mechanotransduction to the control hepatic tumor cellular responses under physical constraints in 3D cultures. We suggest a tentative mechanism, which coordinates signaling rewiring with cytoplasmic restructuring during cell growth in 3D microenvironments.